Pelindungan Hukum Terduga/Tersangka Tindak Pidana Terorisme Dalam Proses Penyelidikan Dan Penyidikan - Ramli Umar (Universitas Islam Indonesia, 2021)
This study aims to analyze first, the procedure of examination and investigation of the Crime of Terrorism. Second, the regulation and implementation of legal protection against presumed and suspects of criminal acts of terrorism in the process of examination and investigating criminal acts of terrorism. This research using juridical methods concludes that the procedure for investigation and investigation of criminal acts of terrorism is carried out based on the Criminal Procedure Code and Law Number 5 of 2018 concerning Terrorism and other related regulations. The law enforcement model in the process of investigating terrorism criminals is more likely to use a crime control model system where law enforcement is given wider and more lax authority in obtaining preliminary evidence. The prosecution process is more likely to use the due process model system. The reason it is more inclined to the due process model is because the prosecution process in terrorism cases is not specifically regulated and follows the guidelines set out in the Criminal Procedure Code.Key Words: Crime of terrorism; examination; investigation; legal protectionAbstrakPenelitian ini bertujuan untuk menganalisis pertama, prosedur penyelidikan dan penyidikan terhadap Tindak Pidana Terorisme. Kedua, pengaturan dan pelaksanaan pelindungan hukum terhadap terduga dan tersangka tindak pidana terorisme dalam proses penyelidikan dan proses Penyidikan Tindak Pidana Terorisme. Penelitian dengan metode yuridis ini menyimpulkan bahwa prosedur penyelidikan dan penyidikan terhadap tindak pidana terorisme dilaksanakan berdasarkan KUHAP dan Undang-undang Nomor 5 Tahun 2018 tentang Terorisme dan aturan terkait lainnya. Model penegakan hukum dalam proses penyelidikan terhadap pelaku tindak pidana terorisme lebih cenderung menggunakan sistem crime control model dimana penegak hukum diberi kewenangan yang lebih luas dan lebih longgar dalam memperoleh bukti permulaan. Proses penuntutan lebih cenderung pada penggunaan sistem due process model. Alasan lebih cenderung pada due process model adalah karena proses penuntutan dalam kasus terorisme tidak diatur secara khusus dan mengikuti pedoman yang di atur dalam KUHAP.Kata Kunci: Pelindungan hukum; pidana terorisme; penyelidikan; penyidikan